Nonlinear Seepage Mathematical Model of Fractured Tight Stress Sensitive Reservoir and Its Application - Yin, Daiyin; Li, Chunguang; Song, Shuang; Liu, Kai (Frontiers in Energy Research, 2022)
The latest advance in the theoretical research of tight reservoir numerical simulation was comprehensively described in this paper. The tight reservoirs must be fractured before they have industrial production value. Therefore, there are artificial fracturing zones and fracturing unmodified zones in tight reservoirs. Irregular fracture networks are formed in the artificial fracturing zones, and there are triple media of matrix, micro fractures and main fractures, but only matrix in the fracturing unmodified zones. There is pressure-sensitive effect and non-Darcy seepage in the matrix, there is unsteady channeling flow between the matrix and micro fractures and main fractures, and there is threshold pressure gradient in the matrix. The flow of fluid between the three media and the transfer flow between the media are complex. The latest generalized pressure-sensitive effect calculation model established by the author of this paper was given. The pressure-sensitive effect of various tight reservoirs can be calculated by using rock physical parameters. In terms of matrix fracture transfer flow law, the matrix/fracture transfer flow calculation model by using the latest matrix nonlinear seepage equation of the tight reservoirs was established by the author of this paper, considering pressure-sensitive effect and threshold pressure gradient. Through experimental verification, the calculation accuracy has been improved by 26 percentage points compared with Warren & Root or Kazemi model. According to the above theory, the triple medium coupling nonlinear mathematical model was established. The developed tight reservoir numerical simulation software was applied to the turbidite tight reservoirs in Wang 587 Block of Jiyang depression of Shengli Oilfield. Compared with the calculation results of Eclipse commercial numerical simulation software, the fitting accuracy has been improved by 13.3%. The calculation results were more in line with the production practice of the tight reservoirs, which showed that the new mathematical model can guide the development of the tight reservoirs more scientifically and effectively.